Modelling Academic Performance in Science-Based Subjects in Primary Schools in Uganda - Wafula, Alfred; Oriangi, George; Odama, Stephene; Ologe, Daniel Ochieng (East African Journal of Education Studies, 2023)
Poor academic performance in science subjects continues to be a major setback in schools of developing countries, despite several interventions to curb the vice. This study investigated the trend in academic performance in mathematics and integrated science in Kigumba town council in Kiryandongo district in Uganda. It used a retrospective cohort analysis design of 8 government-aided and privately funded primary schools while employing documentary analysis to obtain primary leaving examinations (PLE) results. PLE data obtained using documentary analysis was subjected to trend analysis to determine trends in pupils’ performance in the last decade. The findings indicate that performance in mathematics and integrated science in private schools was better than that in government schools over the last decade. In conclusion, teachers in Ugandan government primary schools need to be more committed to teaching mathematics and integrated science so as to improve the academic performance of pupils. In turn, the government and other stakeholders need to provide the necessary prerequisites to enable the teachers to do their work effectively